MISCELLANEOUS BOTANICAL NOTES 2 - KOSTERMANS, A.J.G.H (REINWARDTIA, 1961)
1. Durio cupreus Ridley is considered to represent a distinct species.2. Durio wyatt-smithii Kosterm. is reported from Borneo.3. Machilus nervosa Merr. represents Meliosma bontoeensis Merr.4. Beilschmiedia brassii Allen represents Vavaea brassii (Allen) Kosterm.5. The author of the generic name Heritiera is Aiton.6. Heritiera macrophylla (non Wall.) Merr. is conspecific with H. ungus-tata Pierre.7. Some specimens from N. Celebes, attributed formerly to H. sylvatica Merr., belong to H. arafurensis Kosterm.8. Additional note on Heritiera littoralis Ait. and H. macrophylla Wall, ex Kurz.9. Heritiera montana Kosterm., nov. spec, from New Guinea and H. khidii Kosterm., nov. spec, from Northern Siam.10. Additional note on Heritiera, novoguineensis Kosterm. and H. pereo-riacea Kosterm. and an undescribed species.11. Heritiera acuminata Wall, ex Kurz represents a distinct species.12. Heritiera solomonensis Kosterm., nov. spec, from the Solomon Isl.13. A note on Firmiana bracteata A. DC.14. Firmiana fulgens (Wall, ex King) Corner is based on a mixtum com-positum and has been the source of constant confusion. For the element, which occurs in Malaysia a new name is coined: F. malayana Kosterm. It does not occur in Tenasserim.15. A revised bibliography of Firmiana colorata R. Br., F. pallens Stearn and F. malayana Kosterm. is presented.16. Additional note on Firmiana hainanensis Kosterm.17. Firmiana kerrii (Craib) Kosterm., comb, nov., based on Sterculia kerrii Craib.18. Additional specimens of Firmiana papuana Mildbr.19. Cryptocarya hintonii Allen is referred to Primus as Primus hintonii (Allen) Kosterm.20. Beilschmiedia wallichiana (G. Don) Kosterm., based on Sideroxylon wallichianum, G. Don, is described. Formerly it was relegated to Litsea by Kurz.21. New species in Lauraceae: Beilschmiedia aborensis Kosterm., B. ele-gantissima Kosterm., B. lanatella Kosterm., Persea pomifera Kosterm., Ocotea scandens Kosterm. and Actinodaphne auricolor Kosterm,